2010
DOI: 10.1021/ja910846q
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Mesoporous Silica Nanoparticle Size, Pore Ordering, and Pore Integrity on Hemolytic Activity

Abstract: This paper uses the measure of hemolysis to evaluate the toxicity of nonporous and porous silica nanoparticles with varied sizes and investigates the effects of porous structure and integrity on the nanoparticle-cell interaction. The results show that both nonporous and porous silica cause red blood cell membrane damage in a concentration- and size-dependent manner. In the case of mesoporous silica nanoparticles, the size-dependent hemolysis effect is only present when the nanoparticles have long-range ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
634
6
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(669 citation statements)
references
References 32 publications
27
634
6
2
Order By: Relevance
“…After a 2 h incubation at room temperature, the samples were spun down for the detection of hemoglobin released from hemolyzed RBCs. Surprisingly, contrary to the recently reported trend regarding size, 31 MSNs with larger particle size exhibited a higher hemolytic activity than the small particles ( Figure 2). The hemolytic activity of l-MSNs was first observed at 50 μg mL -1 with 5% hemolysis detected, while a good hemocompatibility (<2% hemolysis) of s-MSN was confirmed at concentrations as high as 100 μg mL -1 .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…After a 2 h incubation at room temperature, the samples were spun down for the detection of hemoglobin released from hemolyzed RBCs. Surprisingly, contrary to the recently reported trend regarding size, 31 MSNs with larger particle size exhibited a higher hemolytic activity than the small particles ( Figure 2). The hemolytic activity of l-MSNs was first observed at 50 μg mL -1 with 5% hemolysis detected, while a good hemocompatibility (<2% hemolysis) of s-MSN was confirmed at concentrations as high as 100 μg mL -1 .…”
Section: Resultscontrasting
confidence: 99%
“…The hemolytic activity of l-MSNs was first observed at 50 μg mL -1 with 5% hemolysis detected, while a good hemocompatibility (<2% hemolysis) of s-MSN was confirmed at concentrations as high as 100 μg mL -1 . While a larger particle size may be preferable for hemocompatible MSNs below 225 nm, 31 increasing particle size of MSNs beyond this range will not necessarily improve the hemocompatibility as one might intuitively expect. In addition to particle size, other factors such as the surface area are also expected to affect the hemolytic potential of MSNs.…”
Section: Resultsmentioning
confidence: 99%
“…Since CPy‐Odot shows the potential as the bright angiography agent, it is necessary to evaluate the hemolytic behaviors of CPy‐Odots on Zebrafish red blood cells (RBCs) 35. RBCs were isolated from the whole blood by centrifugation and purified by five times washing with physiological saline.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it was observed that silanol groups on mesoporous silica structures induce less hemolytic effect compared to rigid spherical nanoparticles possibly due to shape-induced effects, which determine the spatial availability of silanols on the nanoparticle-cell interface. 13 Further, it was observed that: (i) smaller Stöber silica nanoparticles (24 nm) induce a pronounced hemolytic effect when compared with bigger ones (263 nm); 14 (ii) nanostructures with high aspect ratio (nanorods) are more cytotoxic than spherical nanoparticles; 15 (iii) mesoporous silica nanostructures (MSNs) with ordered pores (MCM-41) induce a stronger hemolytic effect compared with non-ordered; 14 (iv) small mesoporous nanoparticles (20 nm) consisted of ethenylenebridged silsesquioxane present very low toxicity 16 and (v) polymers such as PEG (polyethylene glycol) can be used to coat particles in order to greatly reduce the hemolysis. 17 Furthermore, an extensive assessment of the interaction of bare and functionalized porous silica nanomaterials with RBCs concluded that SBA-15-type MSNs cause the deformation of RBCs and consequently lead to their disruption.…”
Section: Introductionmentioning
confidence: 99%